Application of the Preferences Selection Index Method in the Selection of Trainer (Teaching Staff) Khinanti PKBM Case Study - Shely Priselia Deyanti; Sapri Sapri; Prahasti Prahasti (Jurnal Multidisiplin Dehasen (MUDE), 2022)
PKBM Khinanti is a non-formal educational institution center for community learning activities. To get a quality education, a trainer (teaching staff) is needed who is reliable in their field, therefore it is necessary to apply the application of the preferences selection index method in the selection of trainers (teaching staff) for the khinanti pkbm case study. This application can be used to assist the process of assessing trainers (teaching staff) based on predetermined criteria, namely, last education, cumulative index scores, age, and teaching status. Each decision alternative will have these criteria. In this case, to determine the selection of trainers (teaching staff) it is done by summing the weights on each alternative for all attributes, thus this application is able to handle the selection of trainers (teaching staff) so that it will not be difficult to determine the assessment of the selection of trainers (teaching staff).